PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEN KAS PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2012-2017 - Ashari Sofyaun (Yayasan Akrab Pekanbaru, 2018)
This study used accounting profit variables, operating cash flow and curent ratio (CR), and debt to equity ratio (DER). The hypothesis proposed in this study are simultaneous and partial variable accounting profit, operating cash flow, curent ratio and debt to equity ratio influence against cash dividend in companies of the financial sector listed on Indonesia Stock Exchange 2012-2017.The result of simultaneous test (F test) shows that accounting profit, operating cash flow, curent ratio, and debt to equity ratio have significant effect to cash dividend. This can be seen from the results of SPSS showing a level of significance smaller than alpha (0.000 <0.05). Individual significance test results (statistical test t) shows that accounting earnings have a positive effect on cash dividend with a significance level of 0.003 <0.05. Operating cash flows have no effect on cash dividend where the significance level is 0.0679> 0.05. Current ratio is not influence and negative to cash dividend significance level 0.693> 0.05. While the debt to equity ratio has no influence although positive with a significance level of 0.240> 0.05. Keywords: Accounting Profit, Operating Cash Flow, CR, DER, cash dividend.